PENGARUH PENERAPAN PEMBELAJARAN EKSPERIENTIAL LEARNING TERHADAP PENINGKATAN PEMAHAMAN SISWA SEKOLAH DASAR PADA PEMBELAJARAN IPA - Hilman, Irfan; Yusup, Meri (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2017)
AbstractThe influence of the application of learning eksperiential learning to increased understanding students elementary school students learning the IPA. This research aims to know the influence of the use of the learning eksperiential learning and learning verifikatif in IPA learning in primary school (elementary school) to increased understanding of the students on the material energy in class IV. This research uses quasi experiment. Based on the results of the calculation of N-gain understanding of the results of the experimental class for the students of 0,45 with categories and on the control of 0,28 grade with low categories.